2012
DOI: 10.1007/s00248-011-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Reveals Diverse and Distinct Sponge-Specific Microbial Communities in Sponges from a Single Geographical Location in Irish Waters

Abstract: Marine sponges are host to numerically vast and phylogenetically diverse bacterial communities, with 26 major phyla to date having been found in close association with sponge species worldwide. Analyses of these microbial communities have revealed many sponge-specific novel genera and species. These endosymbiotic microbes are believed to play significant roles in sponge physiology including the production of an array of bioactive secondary metabolites. Here, we report on the use of culture-based and culture-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 61 publications
6
59
0
8
Order By: Relevance
“…In the sponges Raspailia ramosa and Stelligera stuposa , 32 and 17% of the Proteobacteria sequences, respectively, were unclassified as opposed to only 1% in the seawater (Jackson et al, 2012). Further exploration suggests that many of our unclassified Proteobacteria OTUs are sponge-specific and the presence of large clusters of sponge-specific and sponge- and coral-specific bacteria in the invertebrates have been described (Simister et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the sponges Raspailia ramosa and Stelligera stuposa , 32 and 17% of the Proteobacteria sequences, respectively, were unclassified as opposed to only 1% in the seawater (Jackson et al, 2012). Further exploration suggests that many of our unclassified Proteobacteria OTUs are sponge-specific and the presence of large clusters of sponge-specific and sponge- and coral-specific bacteria in the invertebrates have been described (Simister et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cultureindependent studies of marine invertebrates have shown similar dominance of members of Endozoicomonas (often incorrectly referred to as the uncharacterized genus 'Spongiobacter' or simply referred to as gammaproteobacteria clones) (e.g. Bellantuono et al, 2012;Bourne & Munn, 2005;Bourne et al, 2008;Cooney et al, 2002;Hansson et al, 2009;Jackson et al, 2012;Kennedy et al, 2008;Kvennefors et al, 2010;Lee et al, 2012;Littman et al, 2009;Lopez et al, 2008;Menezes et al, 2010;Morrow et al, 2012;Pike et al, 2012;Rohwer et al, 2001;Schuett et al, 2007;Zurel et al, 2011). Previous studies have demonstrated that coralassociated Endozoicomonas strains probably contribute to the degradation of sulfur compounds [e.g.…”
Section: Rheinheimera Baltica Osbac1 T (Aj441080)mentioning
confidence: 99%
“…Molecular approaches, such as 16S ribosomal RNA (rRNA) clone libraries (Eichler et al 2006;Gihring et al 2012;Zhang et al 2013a) and polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) (Garrido et al 2014;González-Arenzana et al 2013;Sun et al 2013;Zhang et al 2013b), have greatly increased our comprehension of microbial communities, although these methods poorly represent the rare bacterial groups. In recent years, 454 pyrosequencing has been introduced as a next-generation sequencing method for revealing relatively detailed profiles of microbial communities (Beloshapka et al 2013;Jackson et al 2012). The main advantages of 454 pyrosequencing are a much lower cost per base, the omission of a plasmid cloning step, a large amount of sequence data per run, and long read lengths with an average of up to 400 bps (Glenn 2011;Margulies et al 2005).…”
mentioning
confidence: 99%